Peran Komite Audit Independen Sebagai Pemoderasi Hubungan Antara Environmental Awareness Dan Tanggung Jawab Sosial Perusahaan Dalam Meningkatkan Kualitas Laba Perusahaan Konstruksi Di Indonesia - Darmansyah Darmansyah (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2016)
Achievement of earnings quality is something indispensable for the company, plays an important and central in the world of accounting. That's where the accounting profession is at stake. Corporate Social Responsibility (CSR) to be responsible for the company, and increased public awareness of the importance of protecting the environment is very high. The audit committee has an important role in enhancing the value of the company. The purpose of this study was to analyze the influence of environmental awareness and CSR with the audit committee as moderating in improving the quality of corporate profits construction purposes. The method of analysis using the PLS program Warp 4.0. The results showed that no significant relationship between the environmental awareness of the quality of earnings of construction companies. There is a significant relationship between CSR affects the quality of earnings. While the Independent Audit Committee does not moderate the effect of CSR on Earnings Quality construction companies. Independent Audit Committee has not been instrumental in improving the quality of earnings, but it is expected in the future could increase the role of good corporate governance and monitor the implementation of corporate social responsibility to be better.